(untitled) (European Journal of Education and Psychology, 2018)
One of the most pressing concerns today in our society is how to ensure that students are able to adapt to the ever-changing context in which they live, and one of the ways of achieving this is to ensure good school adjustment. This study analyzes whether this adjustment is influenced by students (and their parents) place of birth, gender and age. The sample group comprised 828 secondary school students (Mean age=14.83; SD=1.81) from the Autonomous Community of the Basque Country (BC) in Spain. The results indicate that students born in the BC to native parents have higher levels of affective engagement and achieve better academic results; however, contrary to expectation, not all natives born to immigrant parents were found to score higher for the different dimensions of school adjustment than those born outside the BC. Also, in general, girls were found to have a higher level of adjustment than boys, and students in the last two years of secondary school had lower levels of performance and engagement than both those in the first two years of secondary school and those in higher education. These results are then discussed in the final part of the paper.